2021
DOI: 10.1177/00131245211028621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mathematics Class Commitment and Anxiety on Mathematics Success: A Path Analysis Study

Abstract: The concepts of commitment and anxiety are essential components of the teaching process, and these concepts come across as the commitment to and concern of mathematics in the field of mathematics learning. This study aims to explore the effect of secondary school students’ mathematics class commitment and anxiety on mathematics success. Another subject studied is the direct and indirect effects of the mathematics class commitment and anxiety on mathematics success. The study is of the quantitative method and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
3
0
4
Order By: Relevance
“…Pendekatan Kajian Kuantitatif Kualitatif Gabungan Kajian Tinjauan Albelbisi et al, 2022;Buzzai et al, 2020;Çağırgan & Soytürk, 2021;Deieso & Fraser, 2019;Donolato et al, 2020;Gabriel et al, 2018;García-Santillán et al, 2022;İlhan et al, 2022;Klee & Miller, 2019;Kyttälä & Björn, 2021;Luu-Thi et al, 2021;Moreno-García et al, 2018;Muwonge et al, 2018;Prahmana et al, 2021;Rončević Zubković et al, 2021;Semeraro et al, 2020;Seo & Lee, 2021;Skaalvik, 2018;Trigueros et al, 2020;Wang et al, 2018;Wang et al, 2020a;Wang et al, 2020b Dari 14 kajian yang mengkaji aspek pencapaian akademik, terdapat 12 kajian mendapati pencapaian akademik mempunyai hubungan korelasi negatif dengan kebimbangan matematik, di mana pencapaian akademik yang rendah akan menyebabkan kebimbangan matematik yang tinggi (Buzzai et al, 2020;Donolato et al, 2020;Gabriel et al, 2018;İlhan et al, 2022;Mann & Walshaw, 2019;Semeraro et al, 2020;Skaalvik, 2018;Suren & Kandemir, 2020;Trigueros et al, 2020;Wang et al, 2020a;Xie et al, 2019;Živković et al, 2022). Hasil dapatan tersebut adalah bertentangan dengan dua lagi kajian, iaitu kajian Kaba dan Şengül (2018) serta Luu-Thi et al (…”
Section: Reka Bentuk Kajianunclassified
See 3 more Smart Citations
“…Pendekatan Kajian Kuantitatif Kualitatif Gabungan Kajian Tinjauan Albelbisi et al, 2022;Buzzai et al, 2020;Çağırgan & Soytürk, 2021;Deieso & Fraser, 2019;Donolato et al, 2020;Gabriel et al, 2018;García-Santillán et al, 2022;İlhan et al, 2022;Klee & Miller, 2019;Kyttälä & Björn, 2021;Luu-Thi et al, 2021;Moreno-García et al, 2018;Muwonge et al, 2018;Prahmana et al, 2021;Rončević Zubković et al, 2021;Semeraro et al, 2020;Seo & Lee, 2021;Skaalvik, 2018;Trigueros et al, 2020;Wang et al, 2018;Wang et al, 2020a;Wang et al, 2020b Dari 14 kajian yang mengkaji aspek pencapaian akademik, terdapat 12 kajian mendapati pencapaian akademik mempunyai hubungan korelasi negatif dengan kebimbangan matematik, di mana pencapaian akademik yang rendah akan menyebabkan kebimbangan matematik yang tinggi (Buzzai et al, 2020;Donolato et al, 2020;Gabriel et al, 2018;İlhan et al, 2022;Mann & Walshaw, 2019;Semeraro et al, 2020;Skaalvik, 2018;Suren & Kandemir, 2020;Trigueros et al, 2020;Wang et al, 2020a;Xie et al, 2019;Živković et al, 2022). Hasil dapatan tersebut adalah bertentangan dengan dua lagi kajian, iaitu kajian Kaba dan Şengül (2018) serta Luu-Thi et al (…”
Section: Reka Bentuk Kajianunclassified
“…Di samping itu, daripada lapan kajian yang mengkaji faktor motivasi, terdapat tujuh kajian yang menunjukkan semakin rendah motivasi seseorang pelajar terhadap subjek matematik, semakin tinggi kebimbangan matematiknya (Çağırgan & Soytürk, 2021;Deieso & Fraser, 2019;Gabriel et al, 2018;İlhan et al, 2022;Salingay et al, 2018, Trigueros et al, 2020Wang et al, 2020a). Walau bagaimanapun, hasil dapatan Wang et al (2018) menunjukkan hasil dapatan yang sebaliknya, iaitu semakin tinggi motivasi seseorang pelajar, semakin tinggi kebimbangan matematiknya.…”
Section: Faktor Diri Sendiriunclassified
See 2 more Smart Citations
“…Jamieson et al (2021) stated that students' exam performance was affected negatively by high mathematics anxiety. Ilhan et al's (2022) research among lower secondary students indicated that those who had higher mathematics anxiety were less successful in performance than those who had lower anxiety. Mathematics anxiety had a negative association with mathematics achievement and solving mathematical problems (Ilhan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%